Research on Transient Process of Electric Locomotive Auto-passing Neutral Section with Load - Liu Ling; Xiong Chenglin (机车电传动)
To theoretically analyze the overvoltage and overcurrent when the train runs through neutral section under traction condition and regeneration condition, the equivalent electrical circuit was developed based on T equivalent circuit of transformer. Then, expressions for the voltage and current under two different conditions at switching time were presented. Based on those expressions, solutions were suggested to avoid overvoltage and overcurrent. Theoretical analysis showed that under traction condition there was intercepting overvoltage at the instant of the switch being turned off and no surge current at the instant of switch being turned on; under regeneration condition intercepting overvoltage occured at the instant of switch being turned on and surge current existed at the instant of switch being turned on. Moreover, there was a big steady current in the latter case, so the rectifier must be blocked. Finally, the validity of the theoretical analysis was verified by simulation results.